NT‐proBNP predicts mortality in adults with transposition of the great arteries late after Mustard or Senning correction - Popelová, J; Tomková, M; Tomek, J (John Wiley & Sons, Inc., 2017)
Objective The patients after Mustard and Senning corrections of transposition of the great arteries (TGA) are at an increased risk of unexpected death. The aim of this study was to identify markers allowing risk stratification of patients after atrial switch correction of TGA to provide them with optimum care. Methods and Results In this study, 87 patients were retrospectively evaluated after atrial switch correction of TGA followed‐up between 2005 and 2015. The mortality during the follow‐up was 9% (8 cardiac deaths). Markers significantly predictive of death using univariable Cox proportional hazard ratio survival analysis were: N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), ejection fraction and end‐diastolic dimension of the systemic right ventricle, mitral E, e′, and s′. Surprisingly, the Doppler parameters of mitral valve in subpulmonary ventricle were more important for prognosis than those of systemic tricuspid valve. In multivariable analysis, the only independent predictors of mortality were NT‐proBNP (P = .00048; AUC 0.97) and the velocity of early diastolic filling (mitral E) in subpulmonary ventricle (P = .01815; AUC 0.81). According to Kaplan–Meier survival analysis, patients with NT‐proBNP > 1000 pg/ml are at high risk of death. Patients with mitral E ≺ 68 cm/s are also at an increased risk of death. Conclusions NT‐proBNP is the most reliable prognostic mortality factor and should be measured regularly in TGA patients after Mustard or Senning correction. Diastolic filling velocity of the subpulmonary left ventricle (mitral E) may be more important for prognosis than systolic function of the systemic right ventricle.